Synthesis and application of hydrophilically-modified Fe3O4 nanoparticles in oil sands separation. Issue 28 (26th April 2018) - Zhang, Zisheng; Li, Hongda; Sui, Hong; He, Lin; Li, Xingang
Abstract : A new kind of hydrophilic magnetic nanoparticle has been synthesized and investigated for the performance in floatation experiments. Abstract : Nanoparticles have been reported to be a promising candidate for the separation of heavy oil from its host rock's surface. These nanoparticles (NPs) are often dispersed and stabilized in the solution by some surfactants during the unconventional oil ores processing. Herein, the PEG600–KH560 (PK) has been grafted onto Fe3 O4 NP surfaces, obtaining a kind of hydrophilically-modified recyclable nanoparticle. Results show that these NPs (averaged at around 16 nm for single sphere) could be well dispersed in water (no settling in 72 h), forming PK-Fe3 O4 nanofluids (NFs) at 0.2 wt%. These PK-Fe3 O4 NFs are found to be able to be quickly separated from the dispersions by an external magnetic field, and returning back to stable NFs when the magnetic field disappears and by shaking. The PK-Fe3 O4 NFs have been further used for the enhancement of heavy oil recovery from oil sands. The floatation results show that the PK-Fe3 O4 NFs could improve oil recovery by at least 12% compared with the traditional hot water extraction process (HWEP). After the extraction, up to 70% of the PK-Fe3 O4 NPs could be directly recycled from the solution for further use. The rest of the NPs are left in the oil phase and attached on the residual solid surface. However, the efficiency of the PK-Fe3 O4 NPs is found to be decreased when the recycling times exceed 5 due to the adsorption of oil components. A mechanistic study shows that the hydrophilic PK-Fe3 O4 NPs could be adsorbed on the mineral surface, making the surface more hydrophilic. The hydrophilic surface and the agitation disturbance helps the liberation process of bitumen from the solid surfaces. On the other hand, when adding the PK-Fe3 O4 NPs into the heavy oil–water system, the oil–water interface is found to be highly modified by the NPs, resulting in significant reduction of the oil–water interfacial tension. The above findings suggest that the PK-Fe3 O4 NPs combined the surface-active role (surfactant) and the nano-size role (adsorption) together, which facilitates its role in oil sands separation.